2022
DOI: 10.1002/ctm2.663
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of dynamic peripheral blood mononuclear cell landscapes in human perioperative anaesthesia/surgery

Abstract: Background The number of patients receiving anaesthesia is increasing, but the impact of general anaesthesia on the patient's immune system remains unclear. The aim of the present study is to investigate dynamics of systemic immune cell responses to anaesthesia during perioperative period at a single‐cell solution. Methods The peripheral blood mononuclear cells (PBMCs) and clinical phenomes were harvested and recorded 1 day before anaesthesia and operation, just after anaesthesia (0 h), and 24 and 48 h after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Although early studies suggested that monocyte function may be suppressed after surgery and anesthesia, 31 , 32 more recent studies indicate an upregulation in the pro-inflammatory functions of monocytes after major surgery. 33 - 35 Here, we confirm that CD14+ monocytes show the greatest changes after elective major surgery, and although delayed compared with trauma, exhibit patterns (upregulation of inflammation pathways and suppression of interferon signaling and MHC-II expression) in common polytrauma patients. MHC-II molecules play a crucial role in the induction of both adaptive immune responses through antigen presentation and the enhancement of innate immune responses via toll-like receptors.…”
Section: Discussionsupporting
confidence: 66%
“…Although early studies suggested that monocyte function may be suppressed after surgery and anesthesia, 31 , 32 more recent studies indicate an upregulation in the pro-inflammatory functions of monocytes after major surgery. 33 - 35 Here, we confirm that CD14+ monocytes show the greatest changes after elective major surgery, and although delayed compared with trauma, exhibit patterns (upregulation of inflammation pathways and suppression of interferon signaling and MHC-II expression) in common polytrauma patients. MHC-II molecules play a crucial role in the induction of both adaptive immune responses through antigen presentation and the enhancement of innate immune responses via toll-like receptors.…”
Section: Discussionsupporting
confidence: 66%
“…Unlike T cells, NK cells can recognize and lyse target cells without the need for prior antigen-specific sensitization but via integrating signals from both killer cell inhibitory receptors (KIRs) and killer cell activatory receptors (KARs). 29 Surgical stress 30 , 31 , 32 and tacrolimus 33 , 34 have been reported to cause phenotypic and functional defects in human NK cells. To date, the function of NK cells in LT has been less studied, or even with controversial results.…”
Section: Resultsmentioning
confidence: 99%